Novel tin(II) butoxides for use as initiators in the ring-opening polymerisation of e-caprolactone - Dumklang M. (2014)
Three tin(II) butoxides, namely: tin(II) n-butoxide, Sn(n-OBu)2; tin(II) i-butoxide, Sn(i-OBu)2; and tin(II) t-butoxide, Sn(t-OBu)2 were synthesized for use as coordination-insertion initiators in the bulk ring-opening polymerisation of e-caprolactone (CL) at 120 °C. Two different methods of synthesis were compared: an old well-established method which gave solid products and a new modified method which, in the case of Sn(n-OBu)2, gave a novel liquid product. The liquid Sn(n-OBu)2 had the advantage for initiation purposes of being much more soluble than the solid Sn(n-OBu)2 due to its lower degree of molecular aggregation, a common characteristic of tin(II) alkoxides which limits their usefulness. Kinetic studies of CL polymerisation by dilatometry showed that the liquid Sn(n-OBu)2 initiator gave a much faster reaction with a higher first-order rate constant (kp = 8.25 l mol-1 min-1) than the solid Sn(n-OBu)2 initiator (kp = 2.96 l mol-1 min-1). The molecular weight of the polymer formed was also hi her. Increasing the bulkiness of the OBu group resulted in solid products with decreased solubility and initiating efficiency (for Sn(i-OBu)2, kp = 2.20 l mol-1 min-1; for Sn(t-OBu)2, kp = 0.69 l mol-1 min-1). It is concluded that the new modified method of initiator synthesis is capable of producing soluble tin(II) alkoxides which have the potential to offer improved kinetic and molecular weight control in the ring-opening polymerisation of cyclic esters.